Spacex - space exploration technologies corporation - Latosha, V. (ТДАТУ, 2018)
SpaceX designs, manufactures and launches advanced rockets and spacecraft. The article provides information about SpaceX foundation and its attaining the ultimate goal of enabling people to colonize Mars and live on other planets. SpaceX розробляє, виробляє та запускає нові ракети та космічні апарати. У статті представлена інформація про заснування SpaceX та досягнення кінцевої мети - надати можливість людям колонізувати Марс та жити на інших планетах
Keywords: заснування SpaceX; інші планети; other planets; big spacecrafts